SI PINTER Sebagai Alat Penghitung Koloni Bakteri Penunjang Laboratorium Mikrobiologi - Salsabila Yunita Kurniawan; Pancawati Ariami; Rohmi Rohmi (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
Colony counter tools are used to count bacterial colonies. The high price constraint makes manual calculation the preferred alternative. In this study, Innovations were made to the SI PINTER tool by replacing the power source with a battery and using digital prayer beads connected to a marker to display the results on the screen. The purpose of this study was to develop the SI PINTER tool as a microbiology laboratory support to improve the accuracy of bacterial colony counts. Standardization of the SI PINTER tool is done by comparing the results of calculations using a conventional Colony Counter and without using equipment (manual) to get accurate results of the number of bacterial colonies. This research method is quasi-experimental and the data was analyzed by One Way ANOVA test. The results of the One Way ANOVA statistical test showed a p-value = 0.996 > 0.05, indicating that there was no significant difference between the results of the number of bacterial colonies using conventional Colony Counter, SI PINTER and manual calculations. The SI PINTER tool can be used according to its function as a microbial colony counter and has portable capabilities because it only relies on electrical energy from batteries